Peluang Industri Kreatif Melalui Pelatihan Pembuatan Video Kreatif Bagi Mahasiswa Akademi Dakwah Indonesia Sumatera Utara - E, Eddy; Usman, Ari; Dafitri, Haida (LPPM STIKOM Tunas Bangsa, 2019)
Submission of da'wah messages can be done in various ways. One of them uses audio-visual media in the form of video that can display elements of images and sound simultaneously. The use of video in the submission of da'wah messages is considered quite effective, because it can reach a wider audience and regional coverage. To be accepted by the audience, besides mastering the propaganda material delivered is demanded by the creativity of the video maker. The video of the work of creativity is part of the creative industry that has economic added value. If the video is distributed through You Tube to gain economic value, the video must collect at least 4,000 hours of watch time in the last 12 months and have a minimum of 1,000 subscribers.